The Palgrave handbook of critical thinking in higher education - Davies, Martin, 1960, March 6-; Barnett, Ronald, 1947- (2015)
"Palgrave Handbook of Critical Thinking in Higher Education explores critical thinking in higher education in all its forms, from definitions to teaching and incorporating it into the curriculum, its relationship to culture and the professions, and its social perspectives and scientific and cognitive manifestations. Davies and Barnett ask what is critical thinking, especially in the context of higher education? The handbook explores these questions, with contributors offering their insight into the contemporary understandings of higher education worldwide"--
"What is critical thinking, especially in the context of higher education? How have research and scholarship on the matter developed over recent past decades? What is the current state of art here? How might the potential of critical thinking be enhanced? What kinds of teaching are necessary in order to realize that potential? And just why is this topic important now? This handbook explores these questions, with contributors offering their insight into the contemporary understandings of higher education worldwide"--
Machine generated contents note: -- Introduction; Martin Davies and Ronald BarnettWhat is Critical Thinking in Higher Education? 1.Critical Thinking: A Streamlined Conception; Robert H. Ennis 2. Critical Thinking and/or Argumentation in Higher Education; Richard Andrews 3.A Curriculum for a Critical Being; Ronald Barnett 4.Willingness to Inquire: The Cardinal Critical Thinking Virtue; Benjamin Hamby Teaching Critical Thinking 5.Teaching Critical Thinking: An Operational Framework; Keith Thomas and Beatrice Lok 6.Teaching Critical Thinking For Lifelong Learning; Paul Green 7.Teaching Critical Thinking As Inquiry; Sharon Bailin and Mark Battersby 8. Debate's Relationship to Critical Thinking; Stephen Llano 9.Thick Critical Thinking: Toward A New Classroom Pedagogy; Milton W. Wendland, Chris Robinson, and Peter A Williams 10. A Disciplined Approach To Critical Thinking; Anna Jones 11. Using Argument Mapping to Improve Critical Thinking Skills; Tim van Gelder Incorporating Critical Thinking in the Curriculum 12. The Relationship Between Self-Regulation, Personal Epistemology, and Becoming a Critical Thinker: Implications for Pedagogy; Iris Vardi 13. Using Argument Diagramming to Teach Critical Thinking in a First Year Writing Course; Maralee Harrell and Danielle Wetzel 14. Virtue and Enquiry: Bridging the Transfer Gap; Justine Kingsbury and Tracey Bowell 15. Proposition Testing: A Strategy to Develop Critical Thinking for Essay Writing; Sara Hammer and Phil Griffiths 16. Conditions for Criticality in Doctoral Education: A Creative Concern; Eva Brodin 17. The Effectiveness of Instruction in Critical Thinking; David Hitchcock Critical Thinking and Culture 18. Do Students from Different Cultures Think Differently about Critical and other Thinking Skills?; Emmanuel Manalo, Takashi Kusumi, Masuo Koyasu, Yasushi Michita, and Yuko Tanaka 19. Critical Thinking through a Multicultural Lens: Cultural Challenges of Teaching Critical Thinking; Maha Bali 20. Cultural Variance, Critical Thinking and Indigenous Knowledges: Exploring a Both-Ways; Henk Huijser and Sharon K. Chirgwin 21. Critical Thinking Education With Chinese Characteristics; Yu DongCritical Thinking and the Cognitive Sciences 22. Metacognitive Education: Going Beyond Critical Thinking ; Joe Lau 23. Applying Cognitive Science to Critical Thinking among Higher Education Students; Jason Lodge, Erin O'Connor, Rhonda Shaw, and Lorelle Burton 24. Metacognition in Critical Thinking: Some Pedagogical Imperatives; Peter Ellerton Critical Thinking and the Professions 25. Critical Thinking In Professional Accounting Practice: Conceptions of Employers and Practitioners; Samantha Sin and Alan Jones 26. Critical Thinking For Future Practice: Learning to Question; Franziska Trede and Celina McEwen 27. Critical Thinking In Osteopathic Medicine: Exploring the relationship between Critical Thinking and Clinical Reasoning; Sandra Grace and Paul J. Orrock 28. Making Critical Thinking Visible in Undergraduates' Experiences of Scientific Research; Anna Wilson, Susan Howitt, Denise Higgins, and Pamela Roberts 29. Using Social Media to Enhance Critical Thinking: Crossing Socio-Educational Divides; Nancy November Social Perspectives on Critical Thinking 30. Speaking Truth To Power: Teaching Critical Thinking in the Critical Theory Tradition; Stephen Brookfield 31. Stumbling Over The First Hurdle: Exploring Notions Of Critical Citizenship; Elmarie Costandius Margaret Blackie, Brenda Leibowitz, Ian Nell, Rhoda Malgas, Sophia Rosochacki, and Gert Young 32. Critical Pedagogy: Critical Thinking as a Social Practice; Stephen Cowden and Gurnam Singh 33. The Knowledge Practices of Critical Thinking; Eszter Szenes, Namala Tilakaratna, and Karl Maton 34. Critical Thinking for Educated Citizenship; Monique Volman and Geert ten Dam.
Includes bibliographical references and index.
Keywords: Critical thinking -- Study and teaching (Higher); EDUCATION / Higher; EDUCATION / Reference; REFERENCE / General